Deconstructing lignocellulosic biomass with a two-step method - WANG XIAOJUAN; FENG HAO; ZHOU BIN; DE FRIAS JOSE ATILIO; WANG BIN (2012)
Lignocellulosic biomass is noted for its recalcitrance to deconstruction as a feedstock for biofuel production. A two-step pretreatment method with the aim of enhancing cellulose digestibility, bypassing the traditional severe pretreatment reaction conditions and improving the overall economics of biofuel production is disclosed herein. A 1st pretreatment step is used to partially remove hemicellulose and lignin. A 2nd pretreatment step using electrolyzed water is used to break the crystalline structure and to remove residual hemicellulose and lignin before enzymatic hydrolysis for releasing fermentable sugars. A digestibility of 95% can be achieved by the two-step approach.